The Effect of Layered Curriculum Supported with Project-Based Learning Method on Students’ Reading and Writing Skills in Turkish Language Education - Sedat Karagül (Elementary Education Online, 2023)
The purpose of this study is to determine the effect of layered curriculum application supported by project based learning method on reading comprehension and written expression skills of students in Turkish language lessons. In line with this objective, an experimental model involving pre-test and posttest applications with control groups was used. The study was conducted at a secondary school located in Çankaya county of Ankara during the first semester of the 2014-2015 school year, in 6th grade Turkish lessons on two groups formed by neutral assignment, one being the experimental group (21 students) and the other being the control group (23 students). In the experimental group, 6 (six) educational situations prepared by the researcher implementing the basic principles of layered curriculum supported by project based learning method, were performed by the course teacher during the semester. In the control group, Turkish language lessons were continued with its known course during the same period by a different teacher. At the end of the study, it was detected that the students in the experimental group scored statistically significantly higher than the students in the control group in the “Turkish Reading Comprehension and Written Expression Skill Test” and wrote more successful essays. With reference to this, it was concluded that layered curriculum supported by project based learning method applied in Turkish language lessons was more effective than the educational concept in which the teaching approaches in the present curriculum are administered.